Abstracts of the Philippine health laws 2006 - Delas Llagas, Lilian A. (National Institutes of Health, University of the Philippines Manila, 2006)
"The National Institutes of Health of the University of the Philippines Manila believes in the importance of disseminating research information. A handbook on Abstracts of Philippine Health Laws 2006 is intended primarily as a handy guide for health practitioners, students and health administrators. Interested members of the law profession may use it in their cases as a quick summary of the pertinent laws. Because law is dynamic, this handbook is the first printing of a series of Abstracts of Philippine Health Laws."--Preface.